Hydrodynamic theory of plasma oscillations in the presence of electron density correlations - Stupka, A.A. (Вопросы атомной науки и техники, 2012)
Hydrodynamics of electronic plasma at presence of correlation of charge density is considered. Equations of ideal hydrodynamics with such condition for the case of immobile ions are received. It is shown that a new variable – second moment of charge density is included in Euler equation, for which temporal equation is received on the basis of equation of continuity in approximation of large radius of equilibrium correlations. Langmuir oscillations in this system are studied, an addition term to frequency of oscillations is found, arising up due to the account of correlation of charge density. Рассмотрена гидродинамика электронной плазмы при наличии корреляции плотности заряда. Получены уравнения идеальной гидродинамики с таким условием для случая неподвижных ионов. Показано, что в уравнение Эйлера входит новая переменная – второй момент плотности заряда, для которого получено временное уравнение на основе уравнения непрерывности в приближении большого радиуса равновесных корреляций. Изучены ленгмюровские колебания в этой системе, найдено значение добавки к частоте колебаний, возникающее благодаря учёту корреляции плотности заряда. Розглянуто гідродинаміку електронної плазми за наявності кореляції густини заряду. Отримані рівняння ідеальної гідродинаміки з такою умовою для випадку нерухомих іонів. Показано, що в рівняння Ейлера входить нова змінна – другий момент густини заряду, для якого отримано часове рівняння на основі рівняння неперервності в наближенні великого радіусу рівноважних кореляцій. Вивчено ленгмюрівські коливання в цій системі, знайдено значення добавки до частоти коливань, що виникає завдяки врахуванню кореляції густини заряду.